Glufosinate Products and Timings for Efficacy in Corn - Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2025)
This study compared several glufosinate-containing herbicides for efficacy in Enlist corn. Treatments were applied at several application timings, including preemergence (PRE), early postemergence (EPOST), postemergence (POST), and late postemergence (LPOST). All herbicides controlled velvetleaf, Venice mallow, and Russian thistle well late in the season. Atrazine PRE followed by Surmise 5, Zalo plus S-metolachlor EPOST, and Zalo EPOST followed by Zalo POST were less effective on Palmer amaranth and kochia than other herbicides by season’s end. For green foxtail, only Zalo plus S-metolachlor EPOST and the atrazine followed by Surmise treatments provided less than 95% control.
Keywords: Sequential applications; Enlist corn